Targeting ocular tissues with intravenously administered aptamers selected by in vivo SELEX - Sonja Korhonen; Katja Stenberg; Umair Seemab; Piia Bartos; Katariina Mäkiniemi; Jørgen Kjems; Daniel Miotto Dupont; Astrid Subrizi (Molecular Therapy: Nucleic Acids)
Ocular diseases create a significant economic burden and decrease in quality of life worldwide. Drugs and carrier molecules that penetrate ocular tissues after intravenous administration are needed for more efficient and patient-friendly treatment of ocular diseases. Here, ocular barrier-penetrating aptamers were selected through the utilization of in vivo SELEX and intravenous injection in rats. Three aptamers—Apt1, Apt2, and Apt5—were chosen based on their specific accumulation in vascularized ocular tissues and further characterized for their in vivo biodistribution using quantitative reverse-transcription PCR (RT-qPCR). A statistically significant difference between ΔCt values of ocular and control tissues with Apt2 (p < 0.0001) and Apt5 (p < 0.0001) was observed. Interestingly, Apt1 was the most abundant aptamer in the sequencing pool, but it did not show a statistically significant difference in in vivo biodistribution between ocular and control tissues. Overall, this study established a functional in vivo SELEX method for discovering ocular tissue targeting aptamers.